Study of Ustaz Hanan Attaki's Da'wah Message on the Instagram Account @hanan_attaki - Baidawi, Baidawi; bin Ismail, Mohd Aashif (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The sophistication of digital media encourages the participation of da'i and enlivens the da'wah event through various Islamic content displayed. This phenomenon opens up opportunities to maximize amar makruf and nahi munkar practically through digital platforms that are democratic and open. Therefore, this research examines Ustad Hanan Attaki's preaching message on the Instagram account @hanan_attaki through content containing aqidah, sharia and moral values displayed in his video reel on Instagram media. This research is qualitative research that applies descriptive and analytical methods in studying Ustad Hanan Attaki's preaching message. Meanwhile, the data collection technique includes selecting content that is relevant to the da'wah message containing the values of faith, sharia and morals on the Instagram account @hanan_attaki as primary data. Secondary data includes journals, the internet and digital traces of Ustad Hanan Attaki. The da'wah theory used in analyzing Hanan Attaki's preaching material contains elements of faith, sharia and morals. The results of this research found that the use of Instagram media on the @hanan_attaki account creates a polite religious climate through creative delivery of da'wah. The narrative video reel displayed is able to represent the values of faith, sharia and morals so as to provide enlightenment amidst the rush of information in today's digital world. Keywords : Da'wah, Da'i, Instagram Media.